DETERMINANTS OF RENAL FUNCTIONAL IMPAIRMENT, THE IMPORTANCE OF FASTING PLASMA GLUCOSE CONTROL: THE NORTHERN SHANGHAI STUDY. (June 2018) - Fan, X.; Xiong, J.; Chi, C.; Teliewubai, J.; Yu, S.; Zhou, Y.; Ji, H.; Zhang, J.; Zhu, M.; Zhang, Y.; Xu, Y.
Abstract : Objective: Chronic kidney disease is a global health problem. However, the causes of renal functional impairment in the general elderly population remains unclear. The aim of this study was to investigate the determinants of renal functional impairment, within a framework of cardiovascular (CV) risk assessment in a community-dwelling elderly cohort. Design and method: From June 2014 to August 2015, a total of 912 community-dwelling elderly subjects (aged > = 65 years) from the northern Shanghai were recruited. CV risk factors were assessed, and renal function was evaluated by estimated glomerular filtration rate (e-GFR) at baseline and during 2-year follow-up. Rapid decline in e-GFR was defined as an e-GFR slope (decline in e-GFR) > 5 ml/min per 1.73 m 2 per year. Results: The average decline in e-GFR was 0.104 ml/min/1.73m 2 per year, while the increasing risk of having rapid decline in e-GFR was 1.25-fold every additional year. Decline in e-GFR was significantly different between diabetics and non-diabetics (p = 0.03). In full adjustment model, decline in e-GFR (p = 0.03) and rapid decline in e-GFR (OR 1.37, CI 1.07–1.75) were both significantly associated with fasting plasma glucose. Similar result of the association of rapid decline in e-GFR with fasting plasma glucose was obtained in the diabetes (full adjustment, OR 1.57, CI 1.05–2.34). Conclusions: In the community-dwelling elderly Chinese, the average decline in e-GFR was 0.104 ml/min/1.73m 2 per year, and renal functional impairment was significantly associated with hyperglycemia in the old Chinese. Figure. No caption available.